Prioritizing Available Islamic Finance Ways, Policies and Strategies in Iranian Commercial Banks (Case Study of Ayandeh Bank) - Seyed Safdar Hosseini; Hassan Mafee; Seyed Fakhreddin Fakhrhosseini (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: Nowadays, one of the multifaceted topics in monetary and banking studies is using the finance of banks and credit institutions. Correctly using finance tools can significantly affect the development of financial markets and economic growth. This article prioritizes available Islamic finance ways, policies, and strategies at Ayandeh Bank.Methodology: This study prioritizes 12 Islamic banks' finance ways by focusing on three criteria of attractiveness and efficiency of the financing method (demand-side acceptance commitments), executive capacities (supply-side institutional compatibility commitments), and macro-environment (bank macro environment). In addition, 30 experts in the field of investment and finance have been collected at Ayandeh Bank. The study also uses the AHP approach.Findings: The results show that foreign currency and Rial deposits have the highest priority, and buying and selling debts, securities, guarantees, and agencies have the lowest priority. Ultimately, a competitive strategy model with the SWOT methodology is proposed for the Islamic finance of Ayandeh Bank to synchronize Ayandeh Bank policies with Iran's business cycles.Originality/Value: Due to prioritizing Islamic financing methods in Ayandeh Bank, these results help bank managers make more appropriate decisions to achieve the bank's goals. Furthermore, the proposed competitive strategy model for Islamic financing provides a suitable model for their plans for synchronizing the bank's policies with Iran's business cycles.